2019
DOI: 10.1111/jsr.12814
|View full text |Cite
|
Sign up to set email alerts
|

Smiling asleep: A study of happy emotional expressions during adult sleep

Abstract: Human foetuses and newborns smile first during sleep, before they smile while awake and interacting with caregivers. Whether smiling persists during adult sleep, and expresses inner joy, is yet unknown. Smiles were looked for during night‐time video‐polysomnography combined with electromyography of the zygomatic and orbicularis oculi muscles in 100 controls, 22 patients with sleepwalking and 52 patients with rapid eye movement (REM) sleep behaviour disorder. Autonomous reactions (heart rate and level of vasoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…This association between REMs and smiles was recently mentioned during REM sleep in adults (Cle et al, 2019). Cecchini et al (2013) have shown, on the contrary, that the number of grouped REMs during AS was negatively correlated to the number of smiles, but positively correlated to the number of cries that occurred during the previous stimulated period of wakefulness.…”
Section: Spontaneous Smiling Related To Rems During Asmentioning
confidence: 68%
See 2 more Smart Citations
“…This association between REMs and smiles was recently mentioned during REM sleep in adults (Cle et al, 2019). Cecchini et al (2013) have shown, on the contrary, that the number of grouped REMs during AS was negatively correlated to the number of smiles, but positively correlated to the number of cries that occurred during the previous stimulated period of wakefulness.…”
Section: Spontaneous Smiling Related To Rems During Asmentioning
confidence: 68%
“…Smiling is an elaborate and complex facial expression, the duration and pattern of which were shown to be similar to that of the adult social smile in our initial study (Challamel et al, 1985). Smiles persist during sleep in adults and also occur in REM sleep: a recent study showed that the majority of these smiles were Grade 2-3, lasted from 0.5 to 6 s, were more frequent in REM than in non-REM sleep, and that 70.5% of them occurred concomitantly to REMs (Cle et al, 2019). This study also showed that half of patients with REM sleep behaviour disorder (RBD) smiled, although that only some controls did.…”
Section: Spontaneous Smiles As In Newborns and Rem Sleep In Adultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Further afield, Gonzaga, Keltner, Londahl, and Smith (2001) showed that DSs correlate with self-report and partner-report estimates of love within romantic relationships. DSs even penetrate sleep; Clé et al (2019) showed that DSs during dreaming are associated with happy dreaming scenarios, reflecting a "true inner mirth." Taken together, these findings support the hypothesis that DSs arise in the presence of felt positive emotions.…”
Section: Hypothesis 1 Dss Reliably Signal Positive Emotion Especially In the Presence Of Pleasant Stimulimentioning
confidence: 99%
“…Clé et al. () from Paris are probably among the first authors not only to write about smiling while being asleep, but also perform an empirical study on this phenomenon. In this study 100 control subjects, 22 patients with sleepwalking and 52 patients with REM sleep behaviour disorder were studied.…”
mentioning
confidence: 99%